IMPLEMENTASI SUPERVISI KEPALA SEKOLAH PADA KOMPETENSI GURU DI PONDOK PESANTREN MTS DARUNNADWAH BEKASI DAN MTS AL- ALIYAH KARAWANG - Ike Nilawati Rohaenah; Hj. Nur Aisah Jamil (Cross-border, 2021)
Supervision of the principal on the (social) competence of teachers is very important because the principal as the leader of the supervisor is obliged to help the teacher to provide support who can carry out their duties both as an educator and as a teacher. Teacher social competence is related to communication skills, attitude and interaction in general, be it with students, fellow teachers, education staff, parents of students to the community at large. The research objective was to obtain results regarding the supervision of the principal on the competence (social) of teachers. The research method used qualitative research. Karawang. Data collection techniques using interviews, observation and documentation. Presentation of data (data display) in narrative data is selected and verified and then concluded. The results show that the principals of MTs Darunnadwah Bekasi and MTs Al-Aliyah Karawang have supervised the social competence of teachers. The teacher has communicated effectively, using good language that is polite and empathic. Able to communicate, both orally and in writing. And able to adapt and carry out their duties as a teacher.